Karstified layers and caves formed by superposed epigenic dissolution along subaerial unconformities in carbonate rocks – Impact on reservoir-scale permeability. (April 2022) - Bagni, Fabio Luiz; Erthal, Marcelle M.; Tonietto, Sandra Nelis; Maia, Rubson P.; Bezerra, Francisco H.; Balsamo, Fabrizio; Córdoba, Valéria C.; de Souza, Flávia G.; Brod, José Affonso; Fernandes, Celso P.; Fonseca, João Paulo T.
Abstract: Superposed events of rock exposure, fracturing, and the hydrological dynamics, are key elements that influence epigenic karstification in carbonate reservoirs. However, they are not fully identified in seismic or well data. One way forward is a multiscale characterization of the porous system to understand karst development, from the pore scale to large caves, confined to high-permeability layers that can reach the basin scale. The present study investigates superposed meteoric dissolution events in carbonate rocks by combining the analyses of depositional setting, diagenesis, stratigraphic architecture, tectonics, and hydrological zones. We performed analyses of 130 plugs collected in 11 outcrops using petrographic, petrophysical, mineralogical, and geochemical analyses. The study area is the Cretaceous Jandaíra Formation in the Potiguar Basin, Brazil, where we identified a regional subaerial unconformity-SU (sequence boundary-1). This surface is characterized by a change in facies and depositional system between dolomitic peritidal deposits (depositional sequence 1) and tight-cemented calcite subtidal deposits (depositional sequence 2). A concentration of caves occurs below the SU. We conclude that subaerial unconformities (vadose surfaces) can develop better reservoir qualities with superposed freshwater leaching and karstification. They control the lateral reservoir zonation, whereas faults and fractures provide vertical pore distribution within the vadose/phreatic hydrological zones. Water table fluctuations can develop multilevel caves and conduits along the epiphreatic zones, increasing the reservoir thickness, which reaches 50–100 m in the Potiguar Basin. We recognized two previous subaerial unconformities at the basin scale using well and seismic data. These findings may have important implications for assessing reservoir location and quality in large areas. Graphical abstract: Image 1 Highlights: We investigate high-permeability karst layers in carbonate units. Caves systems concentrate below subaerial unconformities at the basin scale. Early diagenesis affected peritidal deposits, with dolomitization and karstification. Meteoric fluids cement the overlying subtidal deposits during burial diagenesis. Fractures, unconformities, and hydrology control thickness-extension of reservoir.